2023
DOI: 10.3847/1538-4357/acfc42
|View full text |Cite
|
Sign up to set email alerts
|

A Phase-resolved View of the Low-frequency Quasiperiodic Oscillations from the Black Hole Binary MAXI J1820+070

Qing C. Shui,
S. Zhang,
Shuang N. Zhang
et al.

Abstract: Although low-frequency quasiperiodic oscillations (LFQPOs) are commonly detected in the X-ray light curves of accreting black hole X-ray binaries, their origin still remains elusive. In this study, we conduct phase-resolved spectroscopy in a broad energy band for LFQPOs in MAXI J1820+070 during its 2018 outburst, utilizing Insight-HXMT observations. By employing the Hilbert–Huang transform method, we extract the intrinsic quasiperiodic oscillation (QPO) variability, and obtain the corresponding instantaneous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 111 publications
1
11
0
Order By: Relevance
“…We conducted a phase-resolved analysis using the Hilbert-Huang transform technique, which is a powerful tool for examining nonstationary signals (Huang et al 1998;Huang & Wu 2008). This method has been previously applied in the phaseresolved analysis of QPOs (Su et al 2015;Hsieh & Chou 2020;Shui et al 2023;Yu et al 2023). Two essential steps are involved in this approach: mode decomposition and Hilbert transform analysis.…”
Section: Phase-resolved Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a phase-resolved analysis using the Hilbert-Huang transform technique, which is a powerful tool for examining nonstationary signals (Huang et al 1998;Huang & Wu 2008). This method has been previously applied in the phaseresolved analysis of QPOs (Su et al 2015;Hsieh & Chou 2020;Shui et al 2023;Yu et al 2023). Two essential steps are involved in this approach: mode decomposition and Hilbert transform analysis.…”
Section: Phase-resolved Analysismentioning
confidence: 99%
“…Two essential steps are involved in this approach: mode decomposition and Hilbert transform analysis. Following the approach described in Shui et al (2023), we employed variational mode decomposition, which represents a more advanced method when compared to traditional decomposition techniques (Dragomiretskiy & Zosso 2014). To perform the mode decomposition, we utilized the open-source code vmdpy v0.2 10 (Carvalho et al 2020).…”
Section: Phase-resolved Analysismentioning
confidence: 99%
“…Comptonization is widely considered to be the radiative mechanism behind type-C QPOs (e.g., Bellavita et al 2022;Méndez et al 2022) because observational studies show that the factional rms of type-C QPOs generally increases with photon energy (Zhang et al 2017;Huang et al 2018;Kong et al 2020) and no evident disk-like component is detected in their rms spectra (Sobolewska & Życki 2006;Axelsson et al 2014;Axelsson & Done 2016;Shui et al 2023b). Furthermore, Ma et al (2021) reported the discovery of type-C QPOs above 200 keV, further indicating a strong association with Comptonized emission.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ma et al (2021) reported the discovery of type-C QPOs above 200 keV, further indicating a strong association with Comptonized emission. Additionally, inclination-dependent amplitudes and time lags of type-C QPOs (see Motta et al 2015;van den Eijnden et al 2017), and a QPO phase-dependent reflection component revealed with phase-resolved spectroscopy (see Ingram & van der Klis 2015;Ingram et al 2016Ingram et al , 2017Nathan et al 2022;Shui et al 2023b) may suggest type-C QPOs originate from some geometrical effects. For recent reviews of observations and theories of LFQPOs, the reader is referred to Ingram & Motta (2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation